95.7k views
2 votes
One-half (8 x + 4) + one-third (9 minus 3 x)

User Boram
by
5.6k points

2 Answers

5 votes

Answer:

3x + 5.

Explanation:

factor out 1/6 (1/2 • 1/3)

distribute the 3 from the paranthesis

1/6 (3(8x + 4) + 2(9-3x))

1/6(24x + 12 + 2(9-3x))

distribute 2 through parentheses

1/6(24x+12+18-6x)

collect like terms:

1/6(18x + 12 + 18) > 1/6(18x +30)

factor out 6

1/6 • 6(3x+5)

reduce with GCF (6)

3x + 5

User Mouckatron
by
5.4k points
4 votes

Answer: The simplified expression is: "
3x + 5 " .

______________________________

Explanation:

______________________________

Given the expression:

______________________________

" One-half (8 x + 4) + one-third (9 minus 3x) " ;

We can rewrite that as:


(1)/(2)
(8x+4) + (1)/(3)(9-3x)

Now, let us simplify the expression:

Start with:


(1)/(2)(8x+4) ;

Note the "distributive property" of multiplication:

a(b + c) = ab + ac ;

Likewise:


(1)/(2){(8x +4) = ((1)/(2))8x + ((1)/(2))4=(8)/(2)x +(4)/(2) =4x +2 ; '

Now continue with the remaining part of the expression:


+(1)/(3)(9-3x) ;

Again, use the "distributive property" of multiplication:

a(b + c) = ab + ac ;


+(1)/(3)(9-3x)= ((1)/(3))9+((1)/(3))(-3x)=(9)/(3)+(-(3)/(3)x)=3+(-1x);

= 3 1x ;

= 3 − x ;

________________________________________

Now, combine both terms within the expression; to simplify the expression:


(4x + 2) + (3 -x) ;

Rewrite as:


4x + 2 + 3 - x ;

Now, combine the "like terms":


^+4x -x = 4x -1x = 3x ;


^+2 +3 = 5 ;

The simplified expression is: "
3x + 5 " .

________________________________________

Hope this is helpful to you! Best wishes!

_________________________________________

User Kilise
by
5.2k points